On a nonlocal problem for a quasilinear first-order hyperbolic system with two independent variables - Kmit, I. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A mixed problem with nonlocal conditions on a space variable is considered for a system of quasilinear first-order hyperbolic equations with two independent variables. The sufficient conditions of solvability of this system are given.